Searching for airways biomarkers useful to identify progressive pulmonary fibrosis - Piera Soccio; Giorgia Moriondo; Giulia Scioscia; Valentina Leo; Pasquale Tondo; Luciana Salerno; Paolo Palange; Maria Pia Foschino Barbaro; Donato Lacedonia (BMC Pulmonary Medicine, 2023)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive disorder with unknown etiology. To date, the identification of new diagnostic, prognostic and progression biomarkers of IPF turns out to be necessary. MicroRNA (miRNA) are small non-coding RNAs which negatively regulate gene expression at the post-transcriptional level in several biological and pathological processes. An aberrant regulation of gene expression by miRNA is often associated with various diseases, including IPF. As result, miRNAs have emerged as potential biomarkers with relevance to pulmonary fibrosis. Several reports suggested that miRNAs are secreted as microvesicles or exosome, and hance they are stable and can be readily detected in the circulation. In the contest of miRNAs as circulating biomarkers, different studies show their role in various types of interstitial lung diseases and suggest that these small molecules could be used as prognostic markers of the disease. Exosomes are small, lipid-bound vesicles able to carry various elements of the naïve cells such as proteins, lipids, mRNAs and miRNA to facilitate cell communication under normal and diseases condition. Exosomal miRNAs (exo-miRNA) have been studied in relation to many diseases. However, there is little or no knowledge regarding exo-miRNA in bronchoalveolar lavage (BAL) in IPF. Our study's aim is to evaluate the changes in the expression of two exo-miRNAs in BAL, respectively miR-21 and miR-92a, through highlighting the differences between IPF, progressive pulmonary fibrosis (PPF) and not-progressive pulmonary fibrosis (nPPF). Methods Exosomes were characterized by Western Blot and Multiplex Surface Marker Analysis. Exosomal miRNA expression was performed by qRT-PCR. ANOVA or Kruskal–Wallis test, based on data normality, was used to compare the differential expression between groups. Results MiR-21 expression was significantly higher in the nPPF group than in both IPF and PPF. A result that could point above a possible role of miR-21, as a biomarker in the differential diagnosis between PPF and nPPF. MiR-92a, indeed, was down regulated in PPF compared to IPF and down regulated in PPF compared to nPPF. Conclusions This study demonstrated the putative role of both miR-21 and miR-92a as possible biomarkers of pulmonary fibrosis progression. Moreover, the role of exo-miRNAs is examined as a possible future direction that could lead to new therapeutic strategies for the treatment of progressive and non-progressive pulmonary fibrosis.